2018
DOI: 10.4236/jbm.2018.63002
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Enhanced Recovery after Surgery (ERAS): Use and Surgical Outcome in Breast Cancer Patients

Abstract: Background: ERAS protocols are perioperative interventions aimed at reducing postoperative complications, length of hospital stay (LOS) and early return to normal activities. This has improved outcome in many surgical specialties, including breast surgery. We present the surgical outcome of breast cancer (BC) patients treated over a 12-month period following the principle of ERAS protocols and highlight the underpinning evidence. Methods: A retrospective analysis of all BC patients diagnosed and had breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…65,66 With emerging evidence for the benefits of enhanced recovery after surgery (ERAS) pathways and the shift towards multi-modal analgesia, NSAIDs are currently recommended in an array of pathways and protocols. 74,75 A systematic review investigating the specific role NSAIDs have in both pre-emptive and preventative analgesia for all types of surgery is currently being conducted, 76 the results of which are keenly anticipated. Perhaps the predominant factors in the underutilisation of NSAIDs perioperatively relate to concerns about potential adverse consequences: risk of increased blood loss, acute kidney injury, anastomotic leak, and deleterious effects on bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 With emerging evidence for the benefits of enhanced recovery after surgery (ERAS) pathways and the shift towards multi-modal analgesia, NSAIDs are currently recommended in an array of pathways and protocols. 74,75 A systematic review investigating the specific role NSAIDs have in both pre-emptive and preventative analgesia for all types of surgery is currently being conducted, 76 the results of which are keenly anticipated. Perhaps the predominant factors in the underutilisation of NSAIDs perioperatively relate to concerns about potential adverse consequences: risk of increased blood loss, acute kidney injury, anastomotic leak, and deleterious effects on bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…After the sample is ground and polished, the hardness of the material is measured via the HV-120 Vickers hardness tester. The actual density of the sample is tested following the Archimedes' drainage principle [5]. The actual density calculation equation is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study are consistent with those of other recently reported studies describing multimodal ERP for breast cancer surgery. 2,4,5 However, a unique characteristic of the current study was the observation that not only can postoperative analgesia be achieved with a decreased opioid requirement, but that it also in turn results in a decrease in PONV, a significant problem in breast surgery. One important limitation of the currently available literature including the authors' experience is a lack of reported post-discharge pain scoring, opioid consumption, and antiemetic consumption.…”
Section: Futurementioning
confidence: 95%